Pengaruh Kondisi Sektor Kesehatan terhadap Pertumbuhan Ekonomi di Indonesia - Tasya Aurelya; Nurhayati Nurhayati; Samuel Fery Purba (Jurnal Ekonomi, 2022)
One of the successes of national development is measured by the increasing economic growth of the country and the increasing quality of public health. A nation's capacity to acquire high-quality human resources in order to produce a sustainable economy is greatly influenced by health. The purpose of this study is to represent and analyze the effects of various factors on Indonesia's economic development, including the percentage of smoking in people aged ≥ 15 years (RKK), the health allocation fund (DAK Health), the percentage of children aged less than 6 months who received exclusive breastfeeding (ASI), the percentage of married women aged 15-49 years (KWN) and unmet need health services (LYN). The panel data method and secondary data from BPS (www.bps.go.id) from 2016 to 2020 are used in this study. The test results show that cigarettes indicator have a negative impact, but the DAK Health indicator, ASI indicator, KWN indicator, and LYN indicator, have a positive impact on aggregate economic growth in 34 Indonesian provinces. With the exception of the islands of Sulawesi, Kalimantan, Java, Bali-Nusa Tenggara, and Sumatra, the results of the investigation in 34 provinces of Indonesia show that cigarettes indicator generally have a positive impact. With the exception of the islands of Maluku-Papua, Java, Sumatra, and Bali-Nusa Tenggara, the DAK Health as a whole have a favorable impact. Overall, the ASI indicator have a favorable impact on economic growth, except for the islands of Maluku-Papua and Bali-Nusa Tenggara. KWN indicator have a positive correlation with economic growth in 34 Indonesian provinces. Finally, LYN indicator have a favorable effect on the aggregate in Indonesia, with the exception of the islands of Sulawesi, Maluku-Papua and Bali-Nusa Tenggara.